Local hotspot thermal management using metal foam integrated heat sink. (25th February 2023) - Tikadar, Amitav; Kumar, Satish
Highlights: Metal foam (MF) integrated compound heat sink has been proposed for hot spot thermal management. MF integrated heat sink dissipiates higher heat flux compared to the conventional heat sink. Solid plate fin-MF heat sink layout provides best thermal–hydraulic performance. For solid fin-MF layout, optimum porosity and pore density have been identified. Abstract: Single phase liquid-cooled parallel micro/mini-channel heat sinks are commonly used for electronic cooling because of their superior thermal–hydraulic performance. However, heterogeneous integration of electronic chips, especially in 2.5D and 3D integrated circuits (ICs), results in highly non-uniform heat flux distribution and consequently generates localized hotspots. Conventional micro/mini-channel heat sinks often fail to suffice concentrated local hot spots due to the insufficient heat transfer area and local heat transfer coefficient. Therefore, in this paper, three novel water-cooled aluminum ( A l ) metal foam (MF) integrated compound heat sink layouts, namely solid fin-MF, rectangular fin-MF, and MF heat sink, have been proposed to mitigate local hotspot resulting from non-uniform heat generation. The main concept of the proposed compound heat sinks is to deploy MF in the hotspot region to take advantage of the superior thermal performance of metal foam with minimal pumping power. 3D computational fluid dynamics/heat transfer (CFD/HT) simulations have been performed to quantify and compare the effectiveness of the proposed compound heat sinks with conventional plate-fin heat sink over a wide coolant flow rates/pressure difference Δ P range within the laminar flow regime. Numerical results showed that the solid fin-MF layout provides the best thermal–hydraulic performance compared to all other layouts and offers the highest temperature uniformity, especially at a higher coolant flow rate. Moreover, for the solid fin-MF layout, an optimal porosity and pore density of MF has been identified as 0.9 and 5 PPI (pores per inch), respectively. Finally, at Δ P of 250 Pa and 400 Pa, the optimized solid fin-MF heat sink layout successfully dissipated ∼22.6% and ∼33.4% higher hotspot heat flux compared to the conventional solid fin layout with ∼21% and ∼18.3% lower pumping power penalty while maintaining the peak junction temperature below 85°C.